2018
DOI: 10.1093/cid/ciy917
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin-guided Antibiotic Treatment in Patients With Positive Blood Cultures: A Patient-level Meta-analysis of Randomized Trials

Abstract: Background Whether procalcitonin (PCT)–guided antibiotic management in patients with positive blood cultures is safe remains understudied. We performed a patient-level meta-analysis to investigate effects of PCT-guided antibiotic management in patients with bacteremia. Methods We extracted and analyzed individual data of 523 patients with positive blood cultures included in 13 trials, in which patients were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 25 publications
2
42
0
4
Order By: Relevance
“…A further meta-analysis also revealed, that survival benefit was associated with a PCT algorithm for cessation of antibiotics only, whereas for ICU patients a PCT algorithm for antibiotic initiation or a mixed approach did not reduce mortality [27]. Finally, a meta-analysis focusing on bacteremic patients with positive cultures also found a significant effect of PCT use on antibiotic usage with no evidence for adverse clinical outcomes despite shorter antibiotic durations [28].…”
Section: Trials and Algorithms For Pct-guided Abs In Sepsismentioning
confidence: 92%
“…A further meta-analysis also revealed, that survival benefit was associated with a PCT algorithm for cessation of antibiotics only, whereas for ICU patients a PCT algorithm for antibiotic initiation or a mixed approach did not reduce mortality [27]. Finally, a meta-analysis focusing on bacteremic patients with positive cultures also found a significant effect of PCT use on antibiotic usage with no evidence for adverse clinical outcomes despite shorter antibiotic durations [28].…”
Section: Trials and Algorithms For Pct-guided Abs In Sepsismentioning
confidence: 92%
“…Therefore, PCT has been shown to be able to help decision-making for both initiation and cessation of antibiotic treatment in patients with LRTIs 36,[38][39][40] and is widely recognised as an effective biomarker for bacterial infection 36,41,42 . In a meta-analysis of 12 studies, PCT was compared to CRP and the diagnostic accuracy of PCT was shown to be higher than that of CRP among patients hospitalised for suspected bacterial infections 43 .…”
Section: Diagnostic Value Of Procalcitoninmentioning
confidence: 99%
“…We conducted a secondary analysis using our updated individual patient database [11,14,15,[24][25][26][27]. The study selection and data collection was based on the original protocol published in the Cochrane Library [28] and the report was prepared following the Preferred Reporting Items for Systematic Review and Meta-Analysis individual participant data guidelines [29,30].…”
Section: Patient Population and Trial Selectionmentioning
confidence: 99%